Inflammation-related cancer or cancer-related inflammation - T.g, Shrihari (The European Research Journal, 2018)
Inflammation is the body’s defensive action against various stimuli such as physical or chemical or infectious agents. Acute inflammation and their mediators help in tissue repair and healing. If the inflammation aggravates chronically, non-resolved, dysregulated immune system, results release of various inflammatory mediators such as free radicals (ROS and RNS), cytokines, chemokines, growth factors and proteolytic enzymes produced by innate and adaptive immune cells activate transcriptional factors (NF-KB,STAT3 and HIF-1α) results in cell proliferation, angiogenesis, immunosuppression, genetic instability, invasion and metastasis. Oncogenes related to cancer activate inflammatory mediators such as chemokines and cytokines, which alters the inflammatory tumor microenvironment, promotes tumor progression. This article highlights about the role of inflammation and oncogenes activate inflammatory mediators in tumor progression.